Differential Dynamics of Transposable Elements during Long-Term Diploidization of Nicotiana Section Repandae (Solanaceae) Allopolyploid Genomes - Parisod, Christian (Public Library of Science, 2012)
Evidence accumulated over the last decade has shown that allopolyploid genomes may undergo drastic reorganization. However, timing and mechanisms of structural diploidization over evolutionary timescales are still poorly known. As transposable elements (TEs) represent major and labile components of plant genomes, they likely play a pivotal role in fuelling genome changes leading to long-term diploidization. Here, we exploit the 4.5 MY old allopolyploid Nicotiana section Repandae to investigate the impact of TEs on the evolutionary dynamics of genomes. Sequence-specific amplified polymorphisms (SSAP) on seven TEs with expected contrasted dynamics were used to survey genome-wide TE insertion polymorphisms. Comparisons of TE insertions in the four allopolyploid species and descendents of the diploid species most closely related to their actual progenitors revealed that the polyploids showed considerable departure from predicted additivity of the diploids. Large numbers of new SSAP bands were observed in polyploids for two TEs, but restructuring for most TE families involved substantial loss of fragments relative to the genome of the diploid representing the paternal progenitor, which could be due to changes in allopolyploids, diploid progenitor lineages or both. The majority of non-additive bands were shared by all polyploid species, suggesting that significant restructuring occurred early after the allopolyploid event that gave rise to their common ancestor. Furthermore, several gains and losses of SSAP fragments were restricted to N. repanda, suggesting a unique evolutionary trajectory. This pattern of diploidization in TE genome fractions supports the hypothesis that TEs are central to long-term genome turnover and depends on both TE and the polyploid lineage considered.